يسينودنلإا داصتقلإا ةملسأ وحن (DSN-MUI) ةينطولا ةيعرشلا ةئيهلا يواتف لوح ةبضتقم ةسارد (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2013)
Economic Islamization is a field of knowledge Islamization project which is a growing trend in the Muslim world where the scholars try to restructure modern knowledge and discipline in line with Islamic epistemological principles. Islamic economics, in particular, receives wide attention among them. The spirit of economic Islamization in Indonesia made or encouraged MUI (Indonesian Ulema Council) to established and developed an institution called Dewan Syari’ah Nasional (National Syariah Boards) that specifically deal with the fatwas (legal judgments) related to products of services of financial institutions like reduction debt, restructuring, reconditioning, debt forgiveness, backup sharing in Musharaka and Mudaraba, etc. The Fatwas issued by National Syariah Boards of Indonesian Ulema Council (DSN-MUI) is interesting to be analyzed and studied , especially in the realm of fiqh itself. In the meantime, pointed out the tendency of labeling of conventional economics to simply label attached Sharia . This certainly invites many questions about the sustainability of the existence of the DSN as a law-keeper to fiqh al-mualamat (Fiqh of Finance) in this country. The paper attempts to observe and examine a number of fatwas issued by DSNMUI related to things above as a very simple conceptual contribution to the spirit of Islamization of economics in Indonesia.